Nutritional and lifestyle habits of European pharmacy undergraduate students - Čakar, Uroš; Šobajić, Sladjana; Vidović, Bojana; Djordjević, Brižita (Progress in Nutrition, 2018)
Aim: Balanced nutrition and healthy lifestyle habits are very important, especially in young population. By this way it is possible to prevent many non-communicable diseases. As a health care professionals, pharmacists have very important role in this mission. The aim of this study was to evaluate basic nutritional knowledge and lifestyle habits of pharmacy undergraduate students in the context of their future health profession. Methods: The study group consisted of 591 European undergraduate pharmacy students. The data related to anthropometry, eating and lifestyle habits were obtained based on self-administered cross-sectional survey. Analysis of gender differences was performed using the chi-square test. Statistically significance was set at p value < 0.05. Results: Anthropometric characteristics of students showed that 10.5 % female students were underweight, while 62.6% of the males were overweight and 0.7% were obese. Regular breakfast had 80.9% of the students. Breakfast skipping was statistically higher in male participants (p<0.05). Only 35% of students reported daily intake of vegetables. Also, low fruit consumption was observed in all students with statistically lower fruit intake in males (p<0.05). Consumption of alcohol, fried food and tobacco was not common among students. Basic principle of balanced nutrition was recognized by 58.4% of study population. Conclusion: Results of our study indicate that European pharmacy students have some unsatisfactory eating habits and nutritional knowledge which is already related to their inadequate nutritional status. Our finding suggests that increased level of nutritional education should be incorporated into European pharmacy curriculum.